Holy fire : art of the digital age - Bernard, Yves; Quaranta, Domenico; iMAL Center for Digital Cultures and Technology, Brussel (Brescia Brussel : fpeditions Brescia iMAL Center for Digital Cultures and Technology Brussel, 2008)
Arcangel, Cory ; Babeli, Gazira ; Boredomresearch ; Bruno, Christophe ; Chatonsky, Gregory ; Chernyshev, Aristarkh ; Chevalier, Miguel ; Cosic, Vuk ; Espenschied, Dragan ; Hope, Shane ; Jodi ; LAB[au] ; Leandre, Joan ; Levin, Golan ; Lialina, Olia ; Mattes, Eva & Franco ; Mealey, Alison ; Napier, Mark ; Reas, Casey ; Sandison, Charles ; Schmitt, Antoine ; Sebti, Yacine ; Shulgin, Alexei ; Simon, John F. Jr. ; Slocum, Paul ; Staehle, Wolfgang ; Stern, Eddo ; UBERMORGEN.COM ; Zanni, Carlo
Publication on the occasion of the exhibition 'Holy fire : art of the digital age' at the iMAL Center for Digital Cultures and Technology in Brussel,18.04.2008 - 30.04.2008
boek